Traditional treatment methods used by psychiatric patients seeking treatment from the University Psychiatric Unit, National Hospital of Sri Lanka - Karandawala, I (My University, 2004)
The subject of this study (N=405) were patients who sought psychiatric treatment at the Department of psychological medicine at the National Hospital of Sri Lanka over a period of 3 months. Traditional practitioners are consulted at some stage by many psychiatric patients. Consultation of a traditional practitioner was significantly higher in among patients with low income and those with a psychiatric disorder. There was no significant different in the age, sex, marital status ,occupation and education level between those who consulted and those who hadn't consulted a traditional practitioner. There was no significant difference between the proportions of patients who delayed more than 6 months to seek psychiatric treatment in the group that sought traditional treatment initially and those who did not use it at any instance.